Reliability and Validity of Achievement Motivation in Physical Education in Elementary School at Cyprus - Anagnostou Γαρύφαλλος; Patsiaouras Αστέριος (Inquiries in Physical Education and Sport, 2010)
AMPET is a test which measures learning motivation in Physical Education, to emphasize even more its importance in educational practice. The AMPET consists of eight subscales: a) learning strategy (LS), b) overcoming obstacles (OO), c) diligence and seriousness (DS), d) competence of motor ability (CMA), e) value of learning (VL), f) tension anxiety (TA), g) failure anxiety (FA), and h) Lie scale (LIE). The main purpose was to confirm the validity and reliability of the AMPET Greek Version, when applied to the Greek Cypriot educational system using confirmatory factor analyses. The participants were 155 fifth and sixth grade elementary school children. Their ages ranged from 10 to 12 years old. The above mentioned eight AMPET subscales have been used and as for the data analyses was used the CFA (Confirmatory Factor Analyses) and the EQS statistics program. Our data confirm the validity of AMPET χ²/d.f =1.65, CFI=.954, RMSEA=.048. After reexamining the loadings of every factor variables and of the rates of dispersal of every variable, which are the result of the eight factors of Nishida’s theory (1988), concerning that one model with the same factors but with a smaller number of variables, could apply better to Greek Cypriot reality and lead to an even more efficient and concise version of the above mentioned measurement tool.